2020
DOI: 10.1039/d0en00747a
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological impact of graphene oxide: toxic effects on the model organism Artemia franciscana

Abstract: The environmental impact of graphene oxide was evaluated on the model organism Artemia franciscana for ecotoxicological studies considering different biological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Indeed, Instar I larvae's lack of critical anatomical formations (i.e., mouth and anus) limits the ingestion and the possible bioaccumulation of compounds which could not be absorbed through the external surface of Artemia due to their not-sufficient lipophilicity or small dimensions, such as PLTX. Our finding is in agreement with previous studies showing that Artemia stage I nauplii are more resistant than adults to some xenobiotics, such as inorganic chemical reagents and elements (copper) [38,39] or nanomaterials [40,41]. Notwithstanding, PLTX effects recorded by our study on A. franciscana cysts hatching and its lethality for adults, as well as the effects on nauplii observed by previous studies, suggest that seawater concentrations of PLTX during Ostreopsis blooms could negatively impact Artemia population in marine zooplankton.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, Instar I larvae's lack of critical anatomical formations (i.e., mouth and anus) limits the ingestion and the possible bioaccumulation of compounds which could not be absorbed through the external surface of Artemia due to their not-sufficient lipophilicity or small dimensions, such as PLTX. Our finding is in agreement with previous studies showing that Artemia stage I nauplii are more resistant than adults to some xenobiotics, such as inorganic chemical reagents and elements (copper) [38,39] or nanomaterials [40,41]. Notwithstanding, PLTX effects recorded by our study on A. franciscana cysts hatching and its lethality for adults, as well as the effects on nauplii observed by previous studies, suggest that seawater concentrations of PLTX during Ostreopsis blooms could negatively impact Artemia population in marine zooplankton.…”
Section: Discussionsupporting
confidence: 93%
“…GBMs are known to accumulate in the gut and gills of different organisms such as amphibians (Lagier et al, 2017), invertebrates (Cavion et al, 2020;Lv et al, 2018) as well as fish where it exert adverse effects (Zheng et al, 2019). Similar observations were made in zebrafish using radiolabeled graphene (Lu et al, 2017) while GO was able to translocate from the water to the brain of zebrafish (Hu et al, 2017).…”
Section: Tablesupporting
confidence: 55%
“…Furthermore, the Based on the results of mortality assay, Zhu et al [63] showed that the acute exposure of Artemia salina larvae (instar I, II, and III) to GO induces significant changes in mortality and morphological and physiological parameters; however, some of the concentration used for treatments of GO were higher (respectively 25, 50, 100, 200, 400, 600 mg/L) than used in this study. On the contrary, in another study [64] a weak toxic effect of GO on Artemia franciscana was shown. The organisms at the adult stage were more sensitive than those at the nauplii instar I.…”
Section: Discussionmentioning
confidence: 83%